Analysis of Critical Thinking Dispositions as a Predictor of Students' Critical Thinking Skills in Biology Learning - Desilia Safitri; Jayanti Syahfitri (AL-ISHLAH: Jurnal Pendidikan, 2023)
Some experts say that critical thinking disposition is a predictor of a person's critical thinking skills. The objective of this study is to assess the extent to which students possess critical thinking disposition, in order to forecast their critical thinking abilities in the context of biology education. This study employed descriptive research using a qualitative methodology, involving 74 students from 2 classes as respondents. The instrument used is CTDBT which includes 7 indicators namely Truth-seeking, Open-mind, Analycity, Systematicity, Self-confidence, Inquisitiveness, and Maturity. The results show that students have critical thinking dispositions in the weak category for maturity indicators, medium categories for indicators of open-mindedness, analyticity, systematicity, and self-confidence, and high categories for indicators of truth-seeking and inquisitiveness. Students at the senior high school level generally have a high curiosity and are always eager to prove the truth of something, but they still seem rushed, vulnerable, and unstable, so they require the development of skills and maturity in making decisions to solve problems.